1995
DOI: 10.1016/1074-7613(95)90051-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced differentiation of precursor mouse CD8+ T cells into cytotoxic CD8+ T cells secreting Th1 or Th2 cytokines

Abstract: Alloantigen-stimulated CD8+ mouse spleen cells, either spontaneously or in the presence of IL-12 or IFN gamma plus anti-IL-4, differentiate into CD8+ T cells secreting a Th1-like cytokine pattern (IL-2 and IFN gamma). IL-4 induced differentiation into CD8+ T cells secreting Th2 cytokines (IL-4, IL-5, IL-6, and IL-10), whereas anti-IFN gamma suppressed the development of CD8+ cells secreting IFN gamma. Clones of IL-4- or IFN gamma-producing CD8+ T cells were relatively stable, as IL-4 or IFN gamma did not cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
377
5
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(398 citation statements)
references
References 49 publications
14
377
5
2
Order By: Relevance
“…Some studies have shown that IL-4-induced CD8 + Tc2 cells still remain, sometimes even have increased cytotoxicity (37)(38)(39)(40). So, the effects of IL-4 on CD8 + T cells may rely on the initial cell status, the presence of other cytokines and the stimulating methods.…”
Section: Endogenous Il-4 Deviates Host Immune Response To An Ineffectmentioning
confidence: 99%
“…Some studies have shown that IL-4-induced CD8 + Tc2 cells still remain, sometimes even have increased cytotoxicity (37)(38)(39)(40). So, the effects of IL-4 on CD8 + T cells may rely on the initial cell status, the presence of other cytokines and the stimulating methods.…”
Section: Endogenous Il-4 Deviates Host Immune Response To An Ineffectmentioning
confidence: 99%
“…1). Contaminating Tc1 cells are invariably found in Tc2 preparations [6,7,11,19]. In all our test conditions, approximately 25% of IFN-cproducing cells were present in the Tc2 cultures (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…The cytolytic activity of Tc2 cells is under discussion. Whereas some investigators have reported on non-cytolytic Tc2 cells [51], others have shown similar [6,19,52] and even slightly higher cytotoxic potential for Tc2 cells [11]. The different results may be, at least in part, due to the purity of the different Tc2 cell preparations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…26,27 IFNg is generally made and secreted by activated T and NK lymphocytes. [28][29][30] It mediates many immune functions, and is important in activating cytotoxic responses against virus-infected cells. IFNg also possesses antiviral activities that are mechanistically similar HCV-activated conditional expression vectors AA Matskevich and DS Strayer to those described for IFNa and IFNb.…”
Section: Discussionmentioning
confidence: 99%